Effects of Integrated Literacy and Content-area Instruction on Vocabulary and Comprehension in the Elementary Years: A Meta-analysis - Hwang, HyeJin; Cabell, Sonia Q.; Joyner, Rachel E. (Scientific studies of reading, 2022)
This study synthesized impacts of integrated literacy and content-area instruction (i.e., science, social studies) on vocabulary and comprehension outcomes in the elementary years (i.e., kindergarten through fifth grade). A systematic search of the extant literature identified 35 (quasi)experimental studies. Random-effects models were used to combine effect sizes across studies. Results of meta-analysis revealed that the overall effects were positive and significant for vocabulary (effect size [ES] = 0.91) and comprehension (ES = 0.40). Moreover, a significant positive effect was observed for standardized comprehension outcomes (ES = 0.25), but not for standardized vocabulary outcomes. Supplementary analysis including studies with content knowledge outcomes demonstrated the positive and significant overall effect for content knowledge (ES = 0.89). In addition, no significant moderators of the effect sizes were found among features of research design and characteristics of interventions, perhaps partly due to the small number of studies. The results of our meta-analysis indicate that integrated literacy and content-area instruction has potential to enhance vocabulary words taught to students and comprehension in the elementary years, with the additional benefit of simultaneously cultivating science and social studies knowledge.